Design and Application of Phased Array Ultrasonic Guided Wave Transducer for Detecting the Anchor Bolts. (October 2020) - Jiang, Haibo; Yue, Xianqiang; Gao, Chao; Ma, Junpeng; Li, Yuke
Abstract: To achieve the defect testing of anchor bolts and other buried anchor bolt systems, a phased array ultrasonic guided wave transducer was designed in this paper. By designing the transducer array type, number of array elements, frequency, chip size and scanning mode, it can effectively avoid the interference of thread reflection signals, improve the signal-to-noise ratio and reliability of defect detection results. The transducer was verified by experiment of simulation sample.